Validating and extending the sport brand personality scale. Issue 2 (14th March 2016) - Mitsis, Ann; Leckie, Civilai
Abstract : Purpose: – The purpose of this paper is to validate Tsiotsou's (2012) sport team brand personality scale in a new country (Australia) and segment (Generation Y) and extend its use from sport teams to individual athletes. This paper also explores the scale's predictive power in an athlete's role model influence. Design/methodology/approach: – An online panel survey with 560 responses from Australian Generation Y consumers was obtained. Structural equation modelling was used to test and validate the scale. Findings: – This paper confirmed the sport team brand personality scale can be applied to an individual athlete. Three dimensions of the scale, namely, competitiveness, morality and authenticity, were found to have predictive power in an athlete's role model influence. Authenticity was the strongest predictor, followed by morality and competitiveness. Practical implications: – Individual athlete brand personality is powerful in influencing how Australian Generation Y consumers identify with their favourite athlete as a role model. These insights assist brand and marketing managers to use athletes as part of their communication strategies regarding brand and product endorsements. Originality/value: – This research addresses Tsiotsou's (2012) call to test the robustness and external validity of the sport team brand personality scale and to empirically test how the scale can predict outcomes. The authors succeeded in validating and extending the sport brand personality scale to an individual athlete level in a new country and consumer segment. The scale was found to have predictive power in an athlete's role model influence.